University Students’ Perceptions of Videotaping as a Teaching Tool in a Public Speaking Course - El Mortaji, Latifa (European Scientific Journal, ESJ, 2018)
The purpose of this study was to investigate the effect of videotaping on college studentsâ€™ public speaking skills development in English as a Foreign Language (EFL) from the learnersâ€™ perspective. Twenty Moroccan freshmen students majoring in Engineering, Business, and Humanities at Al Akhawayn University in Ifrane, Morocco, participated in the study. Using 60 videotaped extemporaneous speeches, pre and post-videotaping surveys together with self-reflection essays, the researcher reports on studentsâ€™ perceptions of and attitudes towards the effectiveness of videotaping on their public speaking competence development. Results revealed that the studentsâ€™ public speaking skills improved over the course of a semester in terms of content, followed by non-verbal communication, verbal communication, organization, and language. In line with some previous research, this study confirms that a combination of videotaping and self-reflection has a major effect on improving students’ public speaking skills, developing confidence of EFL learners, and fostering independent learning